Analisis produksi dan pendapatan pelaku usaha kerupuk udang sebelum dan semasa pandemi covid-19 di Kelurahan Tanjung Solok Kecamatan Kuala Jambi - Nurjanah, Rahma; Mustika, Candra; Ainun Najib, Andi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
Â The aims of this study were (1) to find out and analyze the differences in production and income of shrimp cracker business actors before and during the COVID-19 period in Tanjung Solok Village (2) to find out and analyze the factors that influence shrimp cracker production and business actors in Tanjung Solok Village. The method used uses multiple linear regression analysis. From the results of the Differential Test or Paired Sample T-test, it can be seen that there are differences in the average production of shrimp cracker business actors and there are also differences in the level of shrimp cracker income before and during Covid-19 in Tanjung Solok Village. The results of multiple linear regression it is known that the variable capital elasticity has a significant effect on the production variable of the shrimp cracker business in Tanjung Solok Village, while the elasticity variables of age, level of education and labor have no effect. no significant effect on the production of shrimp cracker business in Tanjung Solok Village. The capital and labor variables have a significant effect on the income of shrimp cracker business actors, the age variable has an effect but not significant on income and the education level variable has no significant effect on shrimp cracker business actors.